Level of hsCRP Maternal Serum During Puerperium of Severe Preeclampsia - Julian Dewantiningrum; Zaki Hetami (Journal of Biomedicine and Translational Research, 2018)
Background: Preeclampsia and eclampsia arestill major problemsin the world. Maternal mortality of severe preeclampsia at the puerperal period is likely to be greater because of the cardiovascular diseases (CVD). HsCRP (high sensitivity C-Reactive Protein) is a usefull prediction for CVD among non preeclamptic patients. Before using hsCRP as a marker for that prediction of cardiovascular event from preeclamptic patient, we should do research to know difference of hsCRP between preeclampsia and normal pregnancy.Objective: To determine the differences levels of hsCRP among severe preeclampsia and normal pregnancyMethod : A cross sectional study was conducted to severe preeclampsia. The inclusion criteria were subjects in puerperal period (2- 6 weeks) with a history of severe preeclampsia and normotensive.Exclusion criteria were puerperal infection, chronic hypertension, metabolic syndrome, caesarean section delivery and refuse to join this research. All subjects were examined the levels of hsCRP maternal serum when blood pressure £140 / 90.Result: Subjects were consist of 26 severe preeclampsia (53%) and 23 normal pregnancy (46.9%). Level of hsCRP in severe preeclampsia was 4.73 +3.57while in normotensive 2.42 +4.14 (p <0.05). Severe preeclampsia group will increase the risk of hsCRP rise as much as 2.5 times compared to the normotensive group.Conclusion:Level of hsCRP in patients with preeclampsia post partum were higher than patients with normal pregnancies.